The Effectiveness Of Using Cooperative Script Method On Students’ English Reading Comprehension At Grade X Of SMA Al-Washliyah 3 Medan - Habibah Yuhlizar Wibowo, Yulia Sari Harahap (ALACRITY : Journal of Education, 2022)
The purpose of this research was to determine the effect of using the Cooperative Script Method in reading comprehension. This research was conducted using experimental research methods. The research subjects were students of class X SMA Al Washliyah 3 Medan in the academic year 2021-2022, with their parallel classes and there were 60 students. Each class consists of 30 students and the entire population is taken as a sample, then divided into two groups. The first group as the experimental group was taught using the Cooperative Script Method, while the second group as the control group was taught without using the Cooperative Script Method. The instrument used to collect the data was a multiple choice test set. Pre-test and post-test were given. Data were collected statistically by applying the t-test formula. The results showed that the observed t was higher than the table value 5,24 > 1.67 at a significant level of 0.05 and the degree of freedom (df) was 58. The null hypothesis was rejected and the alternative was accepted. This implies that reading using the Cooperative Script Method has a significant effect on students' reading comprehension.